2020
DOI: 10.18203/2349-2902.isj20204139
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of single versus multiple gallstone disease in KGH, Visakhapatnam

Abstract: Objective: To evaluate the differences in the presentation, their operative implications and difficulties of single stone versus multiple gall stone disease.Methods: This is a prospective study of a minimum of 60 patients with gall stone disease (Group 1-single, Group 2-multiple) from January 2019 to December 2019 in KGH, Visakhapatnam.Results: More common in females, 40-50 years symptoms and complications, TC count difficult cholecystectomies were more in multiple gall stone pts.Conclusion: Multiple gall ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Similar to our study, Raja et al also reported that surgeons encountered greater difficulty during LC among patients having multiple gallstones. 15 In the multiple gallstones, the small floating stones may not remain in constant touch with the gallbladder mucosa, thereby spreading the inflammation to multiple sites inside the gallbladder. Because the gallbladder and extrahepatic bile duct are drained by lymphatic vessels and lymph nodes in Calot's triangle and along the bile duct, its inflammation results in the formation of adhesions around Calot's triangle and the common duct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, Raja et al also reported that surgeons encountered greater difficulty during LC among patients having multiple gallstones. 15 In the multiple gallstones, the small floating stones may not remain in constant touch with the gallbladder mucosa, thereby spreading the inflammation to multiple sites inside the gallbladder. Because the gallbladder and extrahepatic bile duct are drained by lymphatic vessels and lymph nodes in Calot's triangle and along the bile duct, its inflammation results in the formation of adhesions around Calot's triangle and the common duct.…”
Section: Discussionmentioning
confidence: 99%
“…14 Whereas other studies suggest that multiple stones are more harmful. 15,16 The inflammation and the pathological factors influenced by the number of stones in GB are associated with higher odds of conversion of LC to OC. 10,11 Thus, this study was conducted to investigate and identify clinical, haematological, radiological factors and surgical outcomes associated with single versus multiple gallstones.…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms were dyspepsia seen in 25% and 30%, nausea/ vomiting in 45% and 38% in group 1 and 2 patients respectively. A study by Zhang et al, [17] suggested that LC is the gold standard in the treatment for cholelithiasis. Prophylactic cholecystectomy is justified only high suspicion of life.…”
Section: Discussionmentioning
confidence: 99%